I Am More from Here than from There: The Role of Citizenship Schools in the Construction of Racial Identity Among Older Adult Immigrants - Luis Kong (Adult Education Research Conference, 2008)
The non-formal setting of citizenship schools provide an environment for learning, critical reflection and a space to socially construct a collective racial meaning through dialogue and through a critical understanding of history and identity in the United States. This study will focus on the experiences of Spanish speaking older adult learners as they prepare for the citizenship test and explore their sense of identity as new citizens.
Keywords: citizenship; racial identity; social construction; immigrant; older adults